COMPARISON OF STUDENT LEARNING OUTCOMES USING TEAMS GAMES TOURNAMENT (TGT) AND STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TYPES OF COOPERATIVE LEARNING MODEL - Syahmi Edi; Sri Tia Indah Simamora (Jurnal Pelita Pendidikan, 2023)
This study aims to obtain related information on the comparison of student learning outcomes using two cooperative learning models: Teams Games Tournament (TGT) and Student Teams Achievement Division (STAD) models in Class XI IPA at SMAN 1 Doloksanggul. The research design employed in this study is a type of quasi-experimental research. It was conducted at SMAN 1 Doloksanggul, Humbang Hasundutan Regency, with a population consisting of all students in Class XI IPA at SMAN 1 Doloksanggul. The samples were selected using a random sampling technique. Data was collected through a learning outcomes instrument, which included pretests and posttests. The results of the comparative study on student learning outcomes using the cooperative learning models of Teams Games Tournament (TGT) and Student Teams Achievement Division (STAD) at SMAN 1 Doloksanggul are as follows: A comparison of the posttest results between experimental Class I and experimental Class II, using the Independent Sample T-test, yielded a Sig value (2-tailed) of 0.008, which is less than 0.05. Therefore, Ho (null hypothesis) is rejected, and Ha (alternative hypothesis) is accepted, indicating a significant difference between the average posttest scores in experimental Class I (using the TGT learning model) and experimental Class II (using the STAD learning model). The TGT learning model demonstrated better student learning outcomes, with an average score of 86.14, compared to the STAD learning model, which had an average learning achievement score of 81.91.